MANAGEMENT STRATEGY FOR MANGROVE FOREST RESTORATION IN REALIZING 2030 SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Meilinda Suriani Harefa; M. Ridha Syafii Damanik; M. Taufik Rahmadi; Feni Rahmadani (Proceedings on Engineering Sciences, 2025)
Mangrove is the most productive ecosystem on the planet. Mangrove forests are spread over almost all of Indonesia’s coastal areas, one of the coastal areas with mangrove distribution is the coastal area of Langkat Regency. As an ecosystem that lives in coastal areas, mangrove can provide economic, social, and ecological improvements for the life of mangrove ecosystem and human life, however, mangrove continue to experience threats from various natural and human factors. To maintain the mangrove ecosystem, it’s necessary to carry out sustainable utilization and management pf mangrove, considering that the benefit provided by mangroves are enormous for the life of various ecosystem and human life. One way that can be done is to do mangrove restoration. This study aims to determine the results of efforts to restore mangrove forest in coastal areas and realize the Sustainable Development Goals (SDGs) in Langkat Regency. This research was conducted in Langkat Regency from February to November 2023. The population in this study was all coastal areas in Langkat Regency. The sampling technique in this study used purposive random sampling. The research sample points were divided into 25 plots at 3 different locations: The shoreline plot of Tapak Kuda Village, The pond plot of Dogang Village, and the river channel plot of Dogang Village and Pasar Rawa Village. The results of the study are that the cause of damage to mangrove in Langkat Regency occurs due to high population growth, land conversion into ponds, and felling of trees in coastal areas.